Six Sigma Approach with Integration of FMEA-Fuzzy SWARA-Fuzzy WASPAS to Minimize Bottled Water Defects - Gigih Amayu Pragastio; Annisa Kesy Garside; Thomy Eko Saputro (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
Along with the increasingly tight competition, companies are required to always be consistent in improving the quality of its products. Improvement of product quality can be achieved through minimization or even reduction of product defects. This study aims to minimize defects by providing improvement suggestions based on critical failure modes The Six Sigma approach is adopted to reduce the occurrence of product defects. The FMEA-FSWARA-FWASPAS FMEA method is integrated in the six sigma approach, especially to determine the priority of failure modes and the recommended efforts to minimize failure modes that trigger product defects. FSWARA is used to determine severity, occurrence, and detection weights as failure mode assessment criteria. Meanwhile, determination of the critical failure mode is based on the results of the evaluation using FWASPAS. This research is based on a case study in which 5 types of defects were found, namely, skewness, underfilling, leaks, broken lids, and broken boxes. The main causes lie in the human factor and the machine factor. The results showed that there were 3 critical failure modes, namely, the wrong setting of the cutter timer by the operator, the frequent change in the heater temperature, and material getting damaged